Respuesta :
Explanation:
Since, the rod is present in vertical position and the spring is unrestrained.
So, initial potential energy stored in the spring is [tex]U_{s}[/tex] = 0
And, initial potential gravitational potential energy of the rod is [tex]U_{g} = \frac{mgL}{2}[/tex].
It is given that,
mass of the bar = 0.795 kg
g = 9.8 [tex]m/s^{2}[/tex]
L = length of the rod = 0.2 m
Initial total energy T = [tex]\frac{mgL}{2}[/tex]
Now, when the rod is in horizontal position then final total energy will be as follows.
T = [tex]\frac{1}{2}kx^{2} + I \omega^{2}[/tex]
where, I = moment of inertia of the rod about the end = [tex]\frac{mL^{2}}{3}[/tex]
Also, [tex]\omega = \frac{\nu}{L}[/tex]
where, [tex]\nu[/tex] = speed of the tip of the rod
x = spring extension
The initial unstrained length is [tex]x_{o}[/tex] = 0.1 m
Therefore, final length will be calculated as follows.
x' = [tex]\sqrt{(0.2)^{2} + (0.1)^{2}}[/tex] m
Then, x = [tex]x' - x_{o}[/tex]
x = [tex]\sqrt{(0.2)^{2} + (0.1)^{2}}[/tex] m - 0.1 m
= 0.1236 m
k = 25 N/m
So, according to the law of conservation of energy
[tex]\frac{mgL}{2} = \frac{1}{2}kx^{2} + \frac{1 \times mL^{2}}{2 \times 3}(\frac{\nu}{L})^{2}[/tex]
[tex]\frac{mgL}{2} = \frac{1}{2}kx^{2} + \frac{1}{6}mv^{2}[/tex]
Putting the given values into the above formula as follows.
[tex]\frac{mgL}{2} = \frac{1}{2}kx^{2} + \frac{1}{6}mv^{2}[/tex]
[tex]\frac{0.795 kg \times 9.8 \times 0.2 m}{2} = \frac{1}{2} \times 27 N/m \times (0.1236)^{2} + \frac{1}{6} \times 0.795 \times v^{2}[/tex]
v = 2.079 m/s
Thus, we can conclude that tangential speed with which end A strikes the horizontal surface is 2.079 m/s.
The tangential speed with which end A strikes the horizontal surface is 2.08 m/s.
The given parameters:
- Length of the bar, L = 0.2 m
- Mass of the bar, m = 0.795 kg
- Spring constant, k = 27 N/m
- Unstrained length = 0.1 m
The final length of the spring is calculated as follows;
[tex]x = \sqrt{(0.2)^2 \ + \ (0.1)^2} \\\\x = 0.224 \ m[/tex]
The extension of the spring is calculated as follows;
[tex]\Delta x = x_1 - x_0\\\\\Delta x = 0.224 \ m \ - \ 0.1\ m\\\\\Delta x = 0.124 \ m[/tex]
Apply the principle of conservation of energy;
[tex]P.E_i = P.E_k + K.E_{rot}\\\\\frac{mgL}{2} = \frac{1}{2} k \Delta x^2 \ + \ \frac{1}{2} I \omega\\\\\frac{mgL}{2} = \frac{1}{2} k \Delta x^2 \ + \ \frac{1}{2} (\frac{mL^2}{3} )(\frac{V}{L} )^2\\\\\frac{mgL}{2} = \frac{1}{2} k \Delta x^2 \ + \ \frac{1}{6} (mV^2)\\\\mgL = k \Delta x^2 + \frac{1}{3} (mV^2)\\\\\frac{1}{3} mV^2 = mgL - k \Delta x^2\\\\V^2 = \frac{3(mgL - k \Delta x^2)}{m} \\\\V = \sqrt{\frac{3(mgL - k \Delta x^2)}{m}} \\\\[/tex]
[tex]V = \sqrt{\frac{3(0.795 \times 9.8 \times 0.2 \ - \ 27 (0.124)^2)}{0.795}} \\\\V = 2.08 \ m/s[/tex]
Thus, the tangential speed with which end A strikes the horizontal surface is 2.08 m/s.
Learn more about conservation of energy here: https://brainly.com/question/166559